Rare anatomical variants encountered during laparoscopic cholecystectomy in low resource conditions and the convenient concept of the safe zone of dissection: a prospective observational study at a single center - Muad Gamil M Haidar; Nuha Ahmed H Sharaf; Suha Abdullah Saleh; Prashant Upadhyay (Journal of Minimally Invasive Surgery)
Purpose: The severity of surrounding adhesions, anomalous anatomy, and technical issues are the main factors that complicate cholecystectomy. This study focused on determining the types and frequency of laparoscopic anatomical variations found during laparoscopic cholecystectomy in our limited-resources condition and on defining the safe zone of dissection. Methods : This prospective study was conducted at a single center in Aden, Yemen from 2012 to 2019. A total of 375 patients, comprising 355 females (94.7%) and 20 males (5.3%), presented with symptomatic gallbladders and underwent standard four-port laparoscopic cholecystectomy. The regional laparoscopic variations were evaluated and recorded. Results : Of the 375 patients, 26 (6.9%) had laparoscopic anatomical variations, of whom 19 (73.1%) had vascular variations and seven (26.9%) had ductal variations. The anatomical variations included the following: double cystic artery of separated origin, seven cases (26.9%); Moynihan’s hump, six (23.1%); double cystic artery of single origin, four (15.4%); thin long cystic duct, four (15.4%); subvesical duct, three (11.5%); and cystic artery hocking the cystic duct, two (7.7%). Conclusion : Biliary anatomical variations can be expected in any dissected zone. Most of the detected variants were associated with the cystic artery. An overlooked accessory cysto-biliary communication can cause complicated biliary leakage. A surgeon’s skills and knowledge of laparoscopic anatomical variants are essential for performing a safe laparoscopic cholecystectomy.